Lessons learned from small‐scale coral outplanting intervention at a restoration site on the Great Barrier Reef. (18th December 2021) - Cook, Nathan; Smith, Adam; Songcuan, Al; Cassidy, Daniel; Sartori, Greta; McLeod, Ian
Summary: Scientific, tourism and non‐government organisations collaborated to design and undertake a small‐scale coral outplanting intervention at Fitzroy Island, the Great Barrier Reef (GBR), Cairns, Australia. Activities were implemented to assist recovery of a reef showing signs of reduced coral cover after recent coral bleaching and to trial potential for implementation of work of this kind by community members. In December 2017, 240 coral fragments were collected and deployed on mid‐water coral nursery infrastructure. Ten months later, 96 corals (˜15 cm) were outplanted onto bare sections of the surrounding reef rock at depths of 2–8 m. Monitoring was undertaken to measure changes in coral cover at treatment and control locations to determine the potential of using coral outplanting intervention to assist the recovery of degraded reefs. We found no significant difference in live coral cover between controls and treatment over a 12‐month period. Although statistically insignificant, we observed an increase in live coral cover in treatment plots (9.8%) and control plots (2.2%), indicating natural recovery processes occurring across the reef. Total number of fish species and abundance increased significantly over time. Although the outplanting may not have been needed in this case, as a pilot project and the first coral nursery and active reef restoration project in the GBR Marine Park, the research provided valuable lessons associated with project collaboration and planning, site selection, monitoring and natural recovery vs restoration.